New Modernisme Sunnah - Ginting, Ernawati Beru (UIN Sumatera Utara Medan, 2025)
This article explores the relationship between New Modernism and the Sunnah within contemporary Islamic thought. New Modernism represents a recent wave of reformist interpretations among Muslim intellectuals, seeking to reconcile Islamic tradition with modern values such as human rights, democracy, and rationality. The study investigates how New Modernist thinkers reinterpret the Sunnah not merely as a rigid set of traditions, but as a dynamic source of ethical guidance rooted in the Prophet Muhammad’s historical context. Utilizing a qualitative approach, this research analyzes key figures and texts associated with New Modernism, including the works of reformists from the late 20th to 21st century. It argues that New Modernism offers a contextual and humanistic reading of the Sunnah, emphasizing its moral objectives rather than literal applications. This shift challenges classical hermeneutics and calls for a renewal of Islamic jurisprudence grounded in maqasid al-shari‘ah (the higher objectives of Islamic law). The article concludes that the New Modernist approach to the Sunnah can contribute significantly to contemporary Islamic discourse, especially in addressing global ethical challenges.